Neonatal Medicine - Chubarova, Antonina I. (IntechOpen, 2019)
Neonatology is a new and quickly developing medical specialty. The rate of child and infant mortality and the incidence of adult diseases on life expectancy in any country are strongly dependent on the quality of medical aid to neonates. This is an area of medicine where a lot of new industrial innovations are used in combination with the humanizing of technologies. This book includes information on several aspects of neonatal care beginning with resuscitation in the delivery room and culminating with methods of constructing a parent-friendly atmosphere. It is addressed to neonatologists, obstetricians, pediatricians, nurses, and social workers.